The relationship between service delivery protests and crime in the Sekhukhune District of the Limpopo Province - Aphiri, Mokgadi Johanna (My University, 2016)
The study aimed to determine the relationship between service delivery protests and crime in the Sekhukhune District Municipality. To achieve the study a qualitative approach was adopted. Focus group discussions were held with 10 discussants in each of the municipalities within the Sekhukhune District Municipality (10 in Elias Motsoaledi Municipality, 10 in Ephraim Mogale Municipality, 10 in Greater Tubatse Municipality, 10 in Fetakgomo Municipality, and 10 in Makhuduthamaga Municipality).Thematic analysis were used to analysed data collected from 50 participants. The results revealed that lack of service delivery, corruption, poor housing and unemployment cause service delivery protests. Service delivery protests turn violent due to community frustrations and police presence escalates the violence. Sekhukhune District Municipality members participate in violent service delivery protests due hopelessness and lack of knowledge of participatory mechanisms. Road barricading, tyre burning and vandalism are the nature of criminality associated with service delivery protests. Public protests are caused by a myriad of factors; however the findings indicate that there is a gulf that exists between the public and the municipal authorities. The public voice seems not to be heard by authorities, which leads to the public engaging in public protests. Public protests come only as a last resort, after all public participation avenues have been exhausted including the failure of the authorities to respond timeously to public demands. The study was able to determine the relationship between service delivery protests and crime. Sekhukhune District Municipality need to explore ways for both the invited spaces and invented spaces of participation to co-exist. This will provide for early detection (warning signs) for the levels of frustrations and subsequent protests.
Thesis (M.A. (Criminology)) -- University of Limpopo, 2016
Keywords: Service Delivery; Violence; Protests; Crime; Corruption; Riots -- South Africa -- Limpopo; Demonstrations -- South Africa -- Limpopo; Crime -- South Africa -- Limpopo; Municipal services -- South Africa -- Limpopo